2020
DOI: 10.20524/aog.2020.0457
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory bowel disease pathobiology: the role of the interferon signature

Abstract: The pathogenesis of inflammatory bowel disease (IBD) is still unclear, but includes both inflammatory and autoimmune reactions. Current methodological approaches could better elucidate the cytokine pathways and the genetics involved in the etiopathogenesis of this disease. Interferons (IFNs) are cytokines that play a key role in autoimmune/inflammatory disorders because of their pro-and antiinflammatory properties as well as their immunoregulatory functions. An increased expression of IFN-regulated genes, wide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(51 citation statements)
references
References 124 publications
2
49
0
Order By: Relevance
“…Downregulation of DAB2 in DCs may not be limited to PAMPs but may also be compounded by the effect of the host’s inflammatory mediators. As we discussed earlier, Dab2 it has been identified as a IFNγ-responsive gene in macrophages ( 31 ) and increased mucosal IFNγ is a hallmark of Crohn’s disease and experimental murine colitis ( 64 ). Importantly, consistent with the hypothesis that DAB2 restricts DC immunogenicity, we showed that adoptive transfer of Dab2-deficient DC exacerbated experimental colitis in mice ( 23 ).…”
Section: Dab2 Expression In Immune Cells and Its Role In Inflammatorymentioning
confidence: 97%
“…Downregulation of DAB2 in DCs may not be limited to PAMPs but may also be compounded by the effect of the host’s inflammatory mediators. As we discussed earlier, Dab2 it has been identified as a IFNγ-responsive gene in macrophages ( 31 ) and increased mucosal IFNγ is a hallmark of Crohn’s disease and experimental murine colitis ( 64 ). Importantly, consistent with the hypothesis that DAB2 restricts DC immunogenicity, we showed that adoptive transfer of Dab2-deficient DC exacerbated experimental colitis in mice ( 23 ).…”
Section: Dab2 Expression In Immune Cells and Its Role In Inflammatorymentioning
confidence: 97%
“…A highly upregulated cytokine in IBD is interferon-γ (IFNγ). The role of IFNγ in IBD has been mainly attributed to immune modulation [52]. More recently, it was demonstrated that IFNγ exerts potent activity on vasculature.…”
Section: Host Immune Response and Role Of Inflammation In Ibdmentioning
confidence: 99%
“…The patient often presents tenesmus, blood in the stool, weight loss, diarrhea, flatulence, and abdominal pain, resulting in a substantial decrease in quality of life. Furthermore, it is related to psychological disorders [23,24].…”
Section: Inflammatory Bowel Diseasesmentioning
confidence: 99%